2017
DOI: 10.1080/23322039.2017.1291150
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Takāful and conventional insurance demand: A regional analysis

Abstract: Abstract:In this study, we focused on analysing and differentiating the determinants of conventional insurance and Takāful demand across ASEAN and Middle East Regions. We used panel data econometrics on a sample of 14 Asian countries having both conventional insurance and Takāful over the period [2005][2006][2007][2008][2009][2010][2011][2012][2013][2014]. We applied fixed and random effect regression models to assess the impact of macroeconomic and demographic factors on conventional insurance and Takāful dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
1
19
1
1
Order By: Relevance
“…Activities in clan associations are generally related to religious rituals in the Batak community. Another explanation is provided by Akhter & Khan (2017) who found that urbanisation increased the consumption of life insurance in the ASEAN region. This was due to the level of urbanisation lead to the development of insurance sector.…”
Section: Personal Life Insurance Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Activities in clan associations are generally related to religious rituals in the Batak community. Another explanation is provided by Akhter & Khan (2017) who found that urbanisation increased the consumption of life insurance in the ASEAN region. This was due to the level of urbanisation lead to the development of insurance sector.…”
Section: Personal Life Insurance Modelmentioning
confidence: 99%
“…This result is consistent with the argument that the better the education the ability to manage their own financial risks is also better (Kim & Hanna, 2019). Akhter & Khan (2017) argued in ASEAN countries education negatively affect sharia insurance ownership, this was due to low awareness of the product benefits and features. Saur matua life insurance is still unfamiliar among Bataknese.…”
Section: Saur Matua Life Insurance Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Ismanto (2018) continued his studies with a qualitative approach in the Pekalongan area, that the community has a good level of understanding of Islamic insurance products. According to Akhter and Khan (2017) that financial sector income has a significant effect on Islamic insurance demand. Hidayat (2015) found that education plays an important role in increasing public knowledge about the concepts and principles of Islamic insurance.…”
Section: Introductionmentioning
confidence: 99%